The Persistence of Neuromyths in the Educational Settings: A Systematic Review - Torrijos-Muelas, Marta; González-Víllora, Sixto; Bodoque-Osma, Ana Rosa (Frontiers in Psychology, 2021)
Neuroscience influences education and these two areas have converged in a new field denominated ‘Neuroeducation’. However, the growing interest in the education-brain relationship does not match the proper use of research findings. In 2007, the Organisation for Economic Cooperation and Development (OECD) warned of the misunderstandings about the brain amongst teachers, labelling them as neuromyths. The main objective here is to observe the prevalence of the neuromyths in educators over time. After two decades of publications of research on neuromyths among in-service or prospective teachers, this works presents a systematic scientific review. To select the articles, we used the words: “teachers,” “pre-service teachers,” “neuromyths” combined with the Boolean data type “and.” The search was filtered according to the following criteria: (a) identifiable author, (b) written in English, Spanish, French, Italian or Portuguese, (c) word neuromyth in title, abstract or keywords, (d) research with a participant’s survey, (e) sample focused on educators, (f) peer-review publication index in JCR, SJR or ESCI. The documents were found through Web of Science, Scopus, PubMed, Dialnet, ProQuest, EBSCO-host and Google Scholar. After the search, 24 articles were identified as being of sufficiently high quality for this systematic review. This result highlights that neuromyths are still the subject of attention almost two decades after their definition. The findings present neuromyths as the consequence of a lack of scientific knowledge, a communicative gap between scientists and teachers, and the low-quality information sources consulted by teachers. In addition, the data on protectors and predictors of neuromyths is inconsistent. There is also no standard scientific methodology nor a guideline to determine a new neuromyth. The results show the need to improve the scientific content in higher education and the importance of in-service teacher training. This research justifies the requirement for university professors to be active researchers and to establish a close link with educators from other fields and levels. Neuroeducation will be the bridge that unites scientific knowledge and practical application in education, with a rigorous, standard method for the entire scientific-educational community.